Effect of Complexity on Speech Sound Development: Evidence From Meta-Analysis Review of Treatment-Based Studies - Maggu, Akshay R.; Kager, René; To, Carol K. S.; Kwan, Judy S. K.; Wong, Patrick C. M. (Frontiers in Psychology, 2021)
In the current study, we aimed at understanding the effect of exposure to complex input on speech sound development, by conducting a systematic meta-analysis review of the existing treatment-based studies employing complex input in children with speech sound disorders. In the meta-analysis review, using a list of inclusion criteria, we narrowed 280 studies down to 12 studies. Data from these studies were extracted to calculate effect sizes that were plotted as forest plots to determine the efficacy of complexity-based treatment approaches. The outcome variables of interest were improvement on the treated and generalization to the untreated sounds. Meta-analysis revealed that the exposure to complex input not only promoted improvement in production of complex speech sounds (d=1.08, CI=0.98-1.19) but also facilitated the production of untreated simple speech sounds (d=2.69, CI=1.98-3.54). Overall, the current findings revealed that the exposure to complex input promotes acquisition of both complex and simple speech sounds. The current findings are in line with the models of language learnability. The current findings have implications in the treatment of speech sound disorders.